The Implementation Of Democratic Character Education Through Learning Of Social Science Materials Of Ethical And Cultural Diversity In Elementary School - Framz Hardiansyah; Mas'odi Mas'odi (Journal of Innovation in Educational and Cultural Research, 2022)
Globalization has a positive impact on people's lives, but it also raises some issues, including declining the nation's democratic character. Learning about ethnic and cultural diversity in social studies is shown to be helpful in the development of moral character in children. Based on the above description, this study aims to determine the extent to which students can apply democratic character in their daily lives as a result of the implementation of democratic character education. Interviews, questionnaires, and observation were used to collect data in this study. Descriptive qualitative research using a percentage formula was used. Class V SDN Poja II Sumenep, which included 47 students from various ethnic backgrounds, was used for the study. 3.8 percent more students than last year filled out democratic questionnaires, according to the data. This study concludes that the implementation of democratic character education through social studies learning material on ethnic and cultural diversity in elementary schools is categorized as very good according to the character learning syntax. Students' level of understanding in implementing democratic character in everyday life is categorized as very good. This is because students have carried out all activities by predetermined indicators.